PENGARUH VARIASI DOSIS LARUTAN DAUN BANDOTAN (Ageratumconyzoides L.) TERHADAP MORTALITAS LARVA NYAMUK Aedes sp.SEBAGAI SUMBERBELAJAR BIOLOGI - Dewi, Asih Fitriana (Bioedukasi Jurnal Pendidikan Biologi, 2016)
The objective of this research was to determine (1) whether there is any effect of doses variations of solution bandotan leaves (Ageratum conyzoides L.) on mortality larvae of Aedes sp. (2) doses of leaf bandotan solution (Ageratum conyzoides L.) are effective on mortality of larvae of Aedes sp. (3) the potential results of biological research as a learning resource.This research uses experimental methods , design used was a completely randomized design (CRD) with one control and five treatments, there are: p1: the doses solution of leaves bandotan (Ageratum conyzoides L.) is 30 %, p2: the dosis solution of leaves bandotan (Ageratum conyzoides L.) is 35 % , p3: the dosis solution of leaves bandotan (Ageratum conyzoides L .) is 40 % , p4: the dosis solution of leaves bandotan (Ageratum conyzoides L.)is 45 % , p5: thedoses solution of leaves bandotan(Ageratum conyzoides L.) is 50 % , with each five treatment replicates with 10 larvae of Aedes sp.The population in this research is 400 of larvae Aedes sp. The sample that use in this research is random sample and the sum is 300 larva Aedes sp.This research conducted in 38 B Banjarejo of MJ boardinghouse . Mortality of larvae of Aedes sp. an analyzed was using of Non-parametric test with oneway Anovaof Kruskal-Wallis test.The result of research there are:(1) there is doses variation on mortalities of larvae Aedes sp.(2) doses variation 50% is the best influence on mortality of larvae Aedes sp., (3) theresults ofresearchcould potentiallybe usedas a learning resourcethatcan supportbiologicalcompetencefor students.Kata Kunci: variasi dosis larutan daun bandotan,mortalitas, sumber belajar.